2019
DOI: 10.1055/a-0965-6631
|View full text |Cite
|
Sign up to set email alerts
|

Instant messenger smartphone application for endosonographer/cytopathologist real-time interaction at a distance in EUS-FNA for solid pancreatic lesions

Abstract: Background and study aims Telecytopathology (TCP) may allow proper and timely evaluation of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) specimens. The aim of this study was to evaluate the feasibility of TC through a multiplatform instant messenger smartphone application to evaluate specimens of EUS-FNA of pancreatic solid lesions. Patients and methods Twenty-three patients (14 male/9 female; median age: 56 yr.; age range: 33 – 86) with a solid pancreatic lesion were included. Exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…14 Other authors have reported the use of WM and other applications in endoscopic ultrasound-fine needle aspiration of pancreatic lesions, in self-monitoring of melanoma, and in chemotherapy monitoring. [28][29][30][31] This study also explored emotional expressiveness for eight specific types of emotions and identified those particularly expressed through the textual messages of patients with cancer examined in the sample. The intensity of the scores related to the emotions evaluated is greater for the negative ones.…”
Section: Discussionmentioning
confidence: 99%
“…14 Other authors have reported the use of WM and other applications in endoscopic ultrasound-fine needle aspiration of pancreatic lesions, in self-monitoring of melanoma, and in chemotherapy monitoring. [28][29][30][31] This study also explored emotional expressiveness for eight specific types of emotions and identified those particularly expressed through the textual messages of patients with cancer examined in the sample. The intensity of the scores related to the emotions evaluated is greater for the negative ones.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, reports concerning the use of WM in any oncological setting are almost entirely occasional in the medical literature although it has been reported to be widely employed mainly because of doctors' perception of its advantages [14]. WM and other apps are used in endoscopic ultrasound fine needle aspiration (EUS-FNA) of pancreatic lesions, in self-monitoring melanoma, and chemotherapy monitoring [34][35][36]. Some of us reported the use of WM as a tool for the multidisciplinary management of patients with prostate cancer in daily practice [37].…”
Section: Discussionmentioning
confidence: 99%
“…The 18 included studies comprised 11 full-text articles [25][26][27][28][29][30][31][32][33][34][35] and 7 abstracts/posters. [36][37][38][39][40][41][42] They were published in the time span 2012-2020 and were geographically distributed as follows: 10 from North America, 25,28,31,33,[36][37][38][39][40][41] four from Asia, 26,27,32,35 two from Europe, 29,34 one from South America 30 ; one non stated. 42 These studies involved a total of 684 patients, with the number of subjects per study ranging from 20 to 172.…”
Section: Included Studies Topic Of Interest and Type Of Devicesmentioning
confidence: 99%
“…27,35 Several kinds of smartphones and tablets were used in these works including a Samsung Galaxy Note II, A7, S7, and M20 (Samsung Electronics, Seoul, South Korea), an iPhone 4S with a SkyLight adapter (Apple Inc., Cupertino, CA, USA), an iPhone 6 and 7 (Apple Inc., Cupertino, CA, USA), a Huawei Mate 8 (Huawei Technologies Co. Ltd., Shenzhen, Guangdong, China), a Xiaomi 5S (Xiaomi Inc, Beijing, China), and an iPad Mini 2 (Apple Inc., Cupertino, CA, USA) which were mainly employed for acquiring static images, 26,31,32,34,35,40,42 but also for creating scalable whole slide imaging (sWSI) 32 and analyzing them with artificial neural networks (ANN). 27 Other six papers focused on the utility of mobile devices for ROSE of FNA cytological specimens, 25,26,30,34,36 relying on static or dynamic images generated by iOS (iPhone 5, iPad) and Android (Samsung Galaxy s7) supported devices and remotely transmitted via applications such as Facetime (Apple Inc., Cupertino, CA, USA) and WhatsApp (Facebook Inc., Menlo Park, CA, USA). 37…”
Section: Included Studies Topic Of Interest and Type Of Devicesmentioning
confidence: 99%